A study on the clinical manifestations and the incidence of benign and malignant tumors in a solitary thyroid nodule - V, Rahul Chetan; B, Veeresalingam; M, Kishore Kumar; Durbesula, Prabhas Teja; Rao, Pasupuleti Sreenivasa (International Journal of Research in Medical Sciences, 2017)
Tumors are either benign or malignant. The thyroid nodule, which is usually a clinical manifestation of most of the thyroid disorders, is one among them which has been the subject of controversies with divergent opinions and views. Clinical presentation of thyroid nodules varies widely ranging from solitary nodules to benign and malignant tumors. Thyroid nodules accounts up to 8% of the adult population having palpable nodules. However studies on its incidence in the population residing near seacoast are limited. Hence, the present study is carried in an aim to evaluate the clinico-pathological correlation of solitary thyroid nodule and the incidence of malignancy in the population residing at sea coast. The study is conducted in the Narayana Medical College & Hospital (NMCH), which is situated within 10-15 km radius of the seacoast in Nellore district of Andhra Pradesh, India. In this study, 73 subjects were selected who presented with thyroid swelling which was clinically confirmed as solitary thyroid nodule. Out of 73 cases, 12 cases (16.5%) were found to have malignant lesions with remaining 61 cases (83.5%) being benign lesions. The incidence of malignancy among solitary thyroid nodule subjects is up to 16.5% in the population residing near seacoast. Thus the present study warrants people to consult surgeons for early diagnosis and adequate treatment without being passive as most of these swellings are asymptomatic for long duration.